The electrocardiogram made really easy: Using smallgroup tutorials to teach electrocardiogram interpretation to finalyear medical students - M Jama; J Coetser (South African Medical Association, 2016)
Background. Since the 1990s, studies have reported the inability of medical schools to equip students with knowledge and skills to interpret an electrocardiogram (ECG). This has also been the case at the School of Medicine, University of the Free State, Bloemfontein, South Africa, with external examiners in the final examinations repeatedly commenting on the poor performance of students with regard to interpreting ECGs. Subsequently, the Department of Internal Medicine designed small-group tutorials using animations and analogies as methods to improve the ECG interpretation skills of students.Objectives. To improve students’ ability to interpret ECGs and assess their perceptions of the tutorials.Methods. A questionnaire was administered to 67 final-year medical students after their internal medicine rotation in 2012. The objective of thequestionnaire was to obtain feedback on students’ experiences and perceptions of ECG tutorials.Results. Although the results do not provide evidence that the abovementionedmethods improved the students’ competency to interpret ECGs, the limited findings from their perceptions might assist in the further use and improvement of such an approach to facilitate learning.Conclusion. This article highlights the responsive efforts and willingness of registrars in the Department of Internal Medicine to improve the teachingof a major and frequently used investigation such as the ECG, and how registrars formalised these two methods into tutorials.